DETERMINANTS AND COMPARISON OF INTERNET FINANCIAL REPORTING IN DEVELOPING COUNTRY AND DEVELOPED COUNTRY OF SOUTHEAST ASIA (CASE STUDY: PROPERTY AND REAL ESTATE INDUSTRY IN INDONESIA AND SINGAPORE) - Muthiya Gabriela Malawat (Universitas Gunadarma, 2017)
Internet financial reporting is the inclusion of financial information through the internet or the website, known as a voluntary disclosure does not because the content of disclosure, but because the tools used. There is a view if a company reports their financial reporting through the internet indicates it has good news, and if does not report indicate it has bad news. This research aims to examine the effect of firm size, profitability, and leverage to internet financial reporting measured by index and furthermore to compare the disclosure level of internet financial reporting between property and real estate companies in Indonesia as developing country and Singapore as developed country. Sample in this research is 56 companies. Data in this research obtained from companies annual report in 2013 and internet financial reporting index. The result of this research showed that firm size and profitability significantly affect internet financial reporting, meanwhile leverage did not affects internet financial reporting. Furthermore this research showed Indonesia and Singapore did not have difference in disclosure level of internet financial reporting. Keywords: Financial reporting, internet reporting, financial information